Origins of lifetime health around the time of conception: causes and consequences - Fleming, Tom; Watkins, Adam; Velazquez, Miguel; Mathers, John; Prentice, Andrew; Stephenson, Judith; Barker, Mary; Saffery, Richard; Yajnik, Chittaranjan; Eckert, Judith; Hanson, Mark; Terrence, Forrester; et al. (Elsevier, 2018)
Parental environmental factors, including diet, body composition, metabolism, and stress, affect the health and chronic disease risk of people throughout their lives, as captured in the Developmental Origins of Health and Disease concept. Research across the epidemiological, clinical, and basic science fields has identified the period around conception as being crucial for the processes mediating parental influences on the health of the next generation. During this time, from the maturation of gametes through to early embryonic development, parental lifestyle can adversely influence longterm risks of offspring cardiovascular, metabolic, immune, and neurological morbidities, often termed developmental programming. We review periconceptional induction of disease risk from four broad exposures: maternal overnutrition and obesity; maternal undernutrition; related paternal factors; and the use of assisted reproductive treatment. Studies in both humans and animal models have demonstrated the underlying biological mechanisms, including epigenetic, cellular, physiological, and metabolic processes. We also present a meta-analysis of mouse paternal and maternal protein undernutrition that suggests distinct parental periconceptional contributions to postnatal outcomes. We propose that the evidence for periconceptional effects on lifetime health is now so compelling that it calls for new guidance on parental preparation for pregnancy, beginning before conception, to protect the health of offspring.